Operating characteristics of transcritical CO2 heat pump for simultaneous water cooling and heating - Sarkar J.; Bhattacharyya S. (My University, 2025)
The effects of water-side operating conditions (mass flow rates and inlet temperatures) of both evaporator and gas cooler on the experimental as well as simulated performances (cooling and heating capacities, system coefficient of performance (COP) and water outlet temperatures) of the transcritical CO 2 heat pump for simultaneous water cooling and heating the are studied and revised. Study shows that both the water mass flow rate and inlet temperature have significant effect on the system performances. Test results show that the effect of evaporator water mass flow rate on the system performances and water outlet temperatures is more pronounced (COP increases by 0.6 for 1 kg/min) compared to that of gas cooler water mass flow rate (COP increases by 0.4 for 1 kg/min) and the effect of gas cooler water inlet temperature is more significant (COP decreases by 0.48 for given range) compared to that of evaporator water inlet temperature (COP increases by 0.43 for given range). Comparisons of experimental values with simulated results show the maximum deviation of 5% for cooling capacity, 10% for heating capacity and 16% for system COP.